External fixation to correct tarsal-metatarsal fracture in rock pigeon (Columba livia) - Viana, Diego Carvalho; Rui, Leandro Almeida; Dora, Adriano Barile; Fratini, Paula (Revista Ceres, 2017)
Orthopedic conditions, such as bone fractures, are very common in avian medicine. External fixators have been considered the gold standard for birds, since they allow early movement of the limbs and minimal invasive surgery. Fractures in several bones have been successfully treated in pigeons. However, to the best of our knowledge, this case represents the first report of successful surgical repair of tarsal-metatarsal fracture in rock pigeon. External fixator was made with four 24G catheters, being inserted manually proximal and distal to the fracture and connected with polymerizable acrylic. Radiographic consolidation of fracture was observed 60 days post-surgery and anti-inflammatory and antibiotic protocols were successful on avoiding pain and infection during surgery and bone healing.